Economic Efficiency and Policy Implications of Public-Private Partnership in Urban Water Supply - Heryani, Devy Septi; Nurhetti, Nurhetti (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2024)
This study investigates the role of Public-Private Partnership (PPP) in enchancing economic efficiency in urban water supply and explrores the policy for sustainable service delivery in Bandar Lampung, Indonesia. Aquantitative approach was applied using Data Envelopment Analysis (DEA) to measure efficiency, regression analysis to test determinants of efficiency and Partial Least Square-Structural Equation Modeling (PLS-SEM) to examine the relationships between PPP implementation, public policy, efficiency, and sustainable water service delivery. The result show that PPP significantly improves economic efficiency, although performance varies across periods. Public policy is found to have a direct and indirect influence on service sustainability through efficiency. The mediation effect highlights thet efficiency is a critical mechanism linking policy intervention and long-tem service outcomes.